Bioinformatics approach to processing data from high-throughput sequencing of small RNA molecules - A. A. Zharikova; Yu. V. Vyatkin; A. V. Kiseleva; A. N. Meshkov (Кардиоваскулярная терапия и профилактика, 2025)
High-throughput sequencing of small ribonucleic acid (RNA) molecules is widely used to search for markers of various diseases, as well as to study the regulation of gene expression. The data processing protocol consists of many stages, including the stages of analyzing the initial data quality and sequencing results, mapping and studying the expression profile of the detected small RNA molecules. A whole arsenal of programs and specific packages has already been developed to implement each study step. The instrumental composition of the final bioinformatics protocol is critically important for the correct data processing and study reproduction. This review describes the most universal protocol for processing the results of high-throughput sequencing of small RNA molecules, including all the main stages and the most widely used programs.